Metformin, Macrophage Dysfunction and Atherosclerosis - Feng, Xiaojun; Chen, Wenxu; Ni, Xiayun; Little, Peter J.; Xu, Suowen; Tang, Liqin; Weng, Jianping (Frontiers in Immunology, 2021)
Metformin is one of the most widely prescribed hypoglycemic drugs and has the potential to treat many diseases. More and more evidence shows that metformin can regulate the function of macrophages in atherosclerosis, including reducing the differentiation of monocytes and inhibiting the inflammation, oxidative stress, polarization, foam cell formation and apoptosis of macrophages. The mechanisms by which metformin regulates the function of macrophages include AMPK, AMPK independent targets, NF-κB, ABCG5/8, Sirt1, FOXO1/FABP4 and HMGB1. On the basis of summarizing these studies, we further discussed the future research directions of metformin: single-cell RNA sequencing, neutrophil extracellular traps (NETs), epigenetic modification, and metformin-based combination drugs. In short, macrophages play an important role in a variety of diseases, and improving macrophage dysfunction may be an important mechanism for metformin to expand its pleiotropic pharmacological profile. In addition, the combination of metformin with other drugs that improve the function of macrophages (such as SGLT2 inhibitors, statins and IL-1β inhibitors/monoclonal antibodies) may further enhance the pleiotropic therapeutic potential of metformin in conditions such as atherosclerosis, obesity, cancer, dementia and aging.